CHARACTER VALUES IN THE MENGANGGUN VERSES OF BABY-CRADLING TRADITIONS IN SUBULUSSALAM - Epriadi Kombih; Jusrin Efendi Pohan; Dian Syahfitri (Universitas Bina Bangsa Getsempena, 2025)
This research is aimed to investigate the character value contained in the menganggun verses that used in the ritual of baby-cradling in the province of Subulussalam, Indonesia. This study, therefore, try to: (1) identify the character values present in the menganggun verses which are related to individual character values, social character values, and religious character values, and (2) describe the techniques used to convey these character values in the menganggun verses. This study used a qualitative descriptive method. The data were collected using the observation and note-taking technique from popular menganggun verses manuscripts. The data were analyzed by exploring the chosen menganggun verses to identify the character values inherent in their linguistic and thematic components. The analysis data also observed at the ways the verses were delivered, showing how these methods help get moral messages across in the tradition. The result showed that the character values in the menganggun poetry were related to individual character values, social character values, and religious character values. In terms of individual character, the menganggun poetry teaches the importance of healthy self-esteem without arrogance. Regarding social character, the poetry emphasizes values such as compassion, empathy, tolerance, and social responsibility. In terms of religious character, the menganggun poetry instills values of obedience, piety, gratitude, sincerity, and spiritual well-being. These values integrate the local wisdom of the Singkil culture, which is deeply rooted in Islamic teachings, thus reflecting holistic character education. The techniques for conveying character values in the menganggun poetry include the use of poetic and symbolic language rich in metaphors, advice and prayer approaches, repetition and rhythm techniques, and the incorporation of Islamic values.